Development of a Website-Based Project Monitoring, Evaluation, and Reporting Information System in Community-Based Infrastructure Programs - Putra, I Wayan Kurnia Wiguna; Putera, I Gusti Agung Adnyana; Suryantara P, I Putu Gustave (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
In the Community-Based Infrastructure Program (IBM) organized by the Ministry of Public Works and Housing (PUPR), there are several programs such as SANIMAS, Sanitation LPK, TPS 3R, and the PAMSIMAS Program, which are distributed across various villages and neighborhoods in Bali with a substantial budget. Consequently, this demands that the Commitment Officer (PPK) and their team effectively monitor and evaluate the programs. Time and personnel constraints and the community’s limited understanding of construction processes and aid management pose significant challenges. In this research, website-based software will be developed that has good functionality and quality, so that it can provide information quickly and accurately to PPK and relevant stakeholders involved in the project. The development of an integrated project monitoring, evaluation, and reporting information system (SIMEPP) for the IBM program was designed and built using the waterfall model development method, on the client side (frontend) built using HTML, CSS, and Javascript, while on the server side (backend) built using the Laravel framework with the PHP programming language, data storage using a relational database management system (RDBMS) namely MySQL database and on the web server side using apache to serve the Laravel application. Testing results indicate that this system meets all established criteria and is reliable for effectively and efficiently supporting project monitoring, evaluation, and reporting. The functionality testing yielded a score of 1 (good), reliability testing achieved a success rate of 99.99%, and portability testing demonstrated that the SIMEPP website functions consistently across various major browsers. Keywords: Project management, information system, website